Proteomic analysis reveals that a global response is induced by subinhibitory concentrations of ampicillin. Issue 6 (2nd November 2017) - Xiong, Lina; Liao, Dongjiang; Lu, Xinpeng; Yan, He; Shi, Lei; Mo, Ziyao
ABSTRACT: In this study, a recipient-donor co-culture system was used to research the effect of subinhibitory concentrations of antibiotics on horizontal transmission in bacteria and the influence of antibiotics on protein expression. We employed two-dimensional gel electrophoresis combined with mass spectrometry to compare the protein expression profiles in systems with or without 0.5 × the minimum inhibitory concentration of ampicillin. RT-PCR was used to assess the transcriptional levels of the differentially expressed genes. Fifty-seven different proteins were induced or suppressed. The upregulated proteins were involved in transcription and translation, cell wall synthesis, bacterial SOS response, and detoxifying functions, and the downregulated proteins were involved in metabolism. These results indicated that a global response was induced in the recipient-donor co-culture system by the subinhibitory concentration of ampicillin. Further analysis revealed that a global regulatory network based on key pathways was induced in the system in response to the antibiotic pressure. These findings provide a new, more comprehensive view for research on antibiotic-resistance mechanisms in recipient-donor co-culture.